Flexible Electromagnetic Shielding Materials and Their Fabrication Methods: A Comprehensive Review - Gándara, Selcuk; Volosskiy, William (Journal of Green Energy and Environmental Engineering, 2024)
With the rapid development and increasing complexity of electronic equipment, issues of electromagnetic interference (EMI) and pollution have become increasingly severe, posing potential threats to human health and the stable operation of electronic devices. Traditional metal-based EMI shields are too heavy, rigid and corrosion-prone for emerging flexible electronics; carbon nanomaterials (graphene, CNTs) and soft magnetic oxides (e.g., Fe₃O₄) are now intensively studied because they couple low density, high conductivity, corrosion resistance and mechanical compliance, enabling reflection-plus-absorption shielding in ultrathin films. Through rational composite design and structural optimization, shielding materials can be endowed with significant flexibility, enabling them to maintain high-efficiency shielding performance in complex deformation environments. This review comprehensively summarizes the recent research progress in flexible electromagnetic shielding materials, focusing on an in-depth analysis of material categories, shielding mechanisms, structural designs, and preparation methods. The characteristics and performance of various conductive materials (graphene, CNTs, carbon fibers), magnetic materials (Fe₃O₄, metal-coated fibers), and their composites are discussed. Furthermore, different structural designs, including porous (foams, aerogels) and layered architectures, and their corresponding fabrication techniques (foaming, sol-gel, template methods, vacuum filtration, coating, polymer-assisted methods) are systematically elaborated. Finally, the broad application prospects of these flexible EMI shielding materials are demonstrated by combining specific examples from wearable electronic devices, the aerospace industry, and the medical field. The challenges and future development trends, such as AI-assisted design and self-healing materials, are also outlined.